Factors affecting the productivity of teams - Cotterrell, Theresa (My University, 1996)
Teams have, over the last decade, become a popular feature of workplace design. The basis for this trend Is the belief that teamwork allows Individuals to satisfy more of their work-based needs and should therefore, ultimately, improve performance. Despite the increased implementation of teams across a broad spectrum of organisations, empirical research on teams is still in its formative stages and precisely what contributes to team effectiveness remains elusive. Addressing this need, the present study embodies an exploratory empirical investigation of teams as they are practised at the rock face of a gold mine. The research involved examining a sample of these teams using three specific variables which It was hypothesised, may explain the differences In performance between these teams. More specifically, this study Investigated the impact of Job satisfaction, internal work motivation and perceived psychological participation on team performance. Each of these individual variables was examined using a previously-validated scale. The variables were incorporated into a single questionnaire which was administered In a group session with each Individual in the teams sampled. A team performance measure (m2/man) was obtained directly from the mine. Statistical analysis of this data followed a logical progression. At the outset, a one-way ANOVA was run to assess whether statistically there were significant differences between the teams on each of the factors. Indicating that differences do indeed exist, the results justified the reduction of Individual scores in each team to a single aggregate of that variable for the team. Correlation tests were then run between each of the variables and the team performance measure. The results of this study suggest that there Is a significantly positive relationship between Job satisfaction and team productivity (r=.6376). This runs contrary to much of the previous research examining job satlsfactlon and Individual productivity, although it supports some researchers' suggestion that performance should be more broadly defined. This notion is
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts.
Keywords: Teams in the workplace.; Performance.; Employee motivation.; Job satisfaction.